Defects in Mitochondrial Biogenesis Drive Mitochondrial Alterations in PARKIN-Deficient Human Dopamine Neurons - Kumar, Manoj (Stem Cell Reports, 2020)
Mutations and loss of activity in PARKIN, an E3 ubiquitin ligase, play a role in the pathogenesis of Parkinson's disease (PD). PARKIN regulates many aspects of mitochondrial quality control including mitochondrial autophagy (mitophagy) and mitochondrial biogenesis. Defects in mitophagy have been hypothesized to play a predominant role in the loss of dopamine (DA) neurons in PD. Here, we show that although there are defects in mitophagy in human DA neurons lacking PARKIN, the mitochondrial deficits are primarily due to defects in mitochondrial biogenesis that are driven by the upregulation of PARIS and the subsequent downregulation of PGC-1α. CRISPR/Cas9 knockdown of PARIS completely restores the mitochondrial biogenesis defects and mitochondrial function without affecting the deficits in mitophagy. These results highlight the importance mitochondrial biogenesis versus mitophagy in the pathogenesis of PD due to inactivation or loss of PARKIN in human DA neurons.